Flirting with French : how a language charmed me, seduced me & nearly broke my heart - Alexander, William, 1953- (Algonquin Books of Chapel Hill, 2014)
William Alexander is more than a Francophile. He wants to be French. There's one small obstacle though: he doesn't speak la langue française. In Flirting with French, Alexander sets out to conquer the language he loves. But will it love him back?